Seismic analysis of high-rise mega-braced frame-core buildings. (15th May 2016) - Brunesi, E.; Nascimbene, R.; Casagrande, L.
Highlights: Fibre-based FE models for seismic assessment of super-tall buildings were developed. Mechanical idealizations were constructed to represent bolted and welded connections. NLTHAs were conducted to study the response of mega-frame systems and key components. Effects of bracing systems and outriggers/belt trusses were quantified and discussed. Sensitivity to the structure height was explored comparing two case-study prototypes. Abstract: This work summarizes the results of a series of nonlinear dynamic finite element analyses devoted to assess peculiar aspects in the seismic response of high-rise mega-frame prototypes with outriggers and belt trusses. Thirty- and sixty-storey planar frames, extracted from reference three-dimensional structures composed of an internal symmetric braced core, were designed in accordance with European rules. The core consisted of a concentrically braced frame system, while outriggers were placed every fifteen stories to limit inter-storey drifts and second order effects. Numerical models able to account for material and geometric nonlinearities were developed within an open source platform, using inelastic force-based fibre elements to model structural members and mechanical idealizations to reproduce the behaviour of bolted beam–column and welded gusset-plate connections. Out-of-plane imperfections were explicitly included in the braces to allow for potential buckling mechanisms in both braces and gusset plates. Nonlinear time history analyses (NLTHAs) were performed, in comparison with response spectrum analysis (RSA), aiming to quantify the potential of such systems, when included in the lateral-force resisting system of modern high-rise moment resisting frames (MRFs). Global and local performance were investigated in terms of inter-storey drift and acceleration peak profiles, shear and bending moment demands, as well as axial force–displacement curves and static-to-seismic load ratios in critical braces at different floor levels. Sensitivity to the structure height was explored comparing the responses of the two prototypes. Trends were discussed to show that, if accurately designed and detailed in light of capacity design principles and performance-based design concepts, these systems provide an optimum combination of stiffness and strength.